The Intensity Profile Of Optical Laser Beam In A Linear Medium (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
The work examines the laser beam and its parameters. The optical Kerr effect is also discussed. The refractive index of a material depends on the electric field strength. A laser beam, described as a Gaussian beam, has higher intensity at the center compared to the edges of the beam, so the refractive index increases at the center of the beam. However, the intensity of the laser field gradually decreases along the edge of the beam, resulting in a decrease in the refractive index at the edge of the beam. This phenomenon causes selffocusing of the beam in a nonlinear medium. The article examines the parameters of a Gaussian beam and the origin of the optical Kerr effect